Konsentrasi Total Suspended Partikulat dan Timbal pada Udara Ambien - Juslan; Cicilia Selry Tanri; Abdul Mun'im Thariq; Mohamad Ikbal Riski A. Danial; Andi Khairunnisa Salsabila Putri (Poltekkes Kemenkes Semarang, 2026)
Air pollution is a vital environmental issue, especially in areas close to industrial activities and heavy transportation. Biring Ere Village, located in Pangkep Regency, is vulnerable to air quality degradation due to vehicle mobility and other sectoral activities. The study aims to analyze the concentration of Total Suspended Particulate (TSP) and heavy metal Lead (Pb) in ambient air in Biring Ere Village and compare it with quality standards based on Government Regulation of the Republic of Indonesia No. 22 of 2021 and SNI 7119-3:2017. The research method used was field observation with air sampling using a High-Volume Air Sampler (HVAS), which was then analyzed in the laboratory. Laboratory test results showed that in residential areas, the concentration of TSP was 121 μg/m3 and lead (Pb) was 0.01 μg/m3, while in industrial areas, the concentration of TSP was 216 μg/m3 and the concentration of lead (Pb) was 1.4 μg/m3. Based on a comparison with Government Regulation No. 22 of 2021 and SNI 7119-3:2017, the results show that both parameters are still below the established quality standards (TSP < 230 μg/m³ and Pb < 2 μg/m³). The ambient air quality in Biring Ere Village is categorized as safe. However, the concentration levels of Total Suspended Particulate (TSP) and Lead (Pb) are close to the threshold, requiring special attention in air pollution control efforts to ensure that they remain below the quality standards.